Effect of component and surface structure on poly(l-lactide-co-ɛ- caprolactone) (PLCA)-based composite membrane. (1st October 2019) - Jiang, Liuyun; Xu, Lijuan; Ma, Bingli; Ding, Haojie; Tang, Chunyan; Wang, Jinghui; Tang, Shuo; Su, Shengpei
Abstract: To obtain an ideal guided bone tissue regeneration (GBR) membrane, a novel double-layered composite membrane was developed by combining the technology of solvent casting and electrospinning, which was composed of poly (l -lactide-co-ɛ-caprolactone) (PLCA) cast layer and Mg-substituted nano-hydroxyapatite (Mg- n -HA)/PLCA composite electrospun layer. The effect of different Mg- n -HA contents of 10 wt%, 20 wt%, 30 wt% and 40 wt% and membrane surface porous structure on mechanical properties, in vitro apatite deposit, cell biocompatibility and in vivo tissue regeneration of the composite membrane were investigated, using electronic universal testing machine, scanning electron microscope (SEM), in vitro simulated body fluids (SBF) soaking, cell culture experiment and in vivo skulls repair experiment of rabbits. The results showed that the addition of Mg- n -HA did not bring about negative effect on the mechanical properties, porous structure consisting of nanofibers and the degradation rate of the composite membrane. Instead, the high Mg- n -HA content and membrane surface porous structure greatly promoted the apatite deposit. Moreover, the Mg- n -HA/PLCA composite double-layered membranes displayed better cell proliferation and tissue biocompatibility, suggesting it had a great potential to be used as GBR membrane.